The Lived Experience of Teen Girls' Abortion in Taiwan. (19th July 2014) - Lee, Tsorng-Yeh; Chou, Cheng-Chen; Chen, Chin-Mi; Weng, Min-Hsueh; Liu, Yin-Chun
In-depth interviews about the experience after having an abortion were conducted with 20 teenage girls in Taiwan. Six themes emerged by using Colaizzi's phenomenological methodology: (a) returning to "normal" life as soon as possible, (b) seeking abortion resources, (c) neglecting post-abortion care, (d) disturbed by the fetus ghost, (e) concern about virginity loss and choices for future, and (f) re-examining relationships with partners. Teenage girls received tremendous social and moral pressure due to their traditional cultural and social environment when they went through the abortion experience. The study helps health professionals understand the experience of those girls.